2011
DOI: 10.1590/s0365-05962011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Metástase cutânea rara de provável carcinoma basaloide de cólon simulando granuloma piogênico

Abstract: Acrometastasis is a rare occurrence, especially when affecting the hands. It represents around 0.007-0.2% of all metastatic lesions. The most common site of origin is the lung, accounting for 40-50% of all cases reported in the literature. Kidneys and breasts are other sites also associated with neoplastic lesions that disseminate to the hands. More rarely, the site of origin may be the gastrointestinal tract or other systemic tumors or sarcomas. Early diagnosis is difficult, since the condition may be asympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
6
0
3
Order By: Relevance
“…La manifestación clínica habitual comprende aumento de volumen doloroso, generalmente, similar a una infección de partes blandas con eritema, sensibilidad, calor local y limitación de la funcionalidad que puede evolucionar con empeoramiento progresivo de la lesión pudiendo adquirir un aspecto granulomatoso o asociado a ulceración 1,7 . Dada su presentación pueden simular granulomas piogénicos, artritis reumatoide, neoplasia primarias de piel como carcinoma de células escamosas, focos de osteomielitis, tofos gotosos, entre otros; debiendo tener un alto índice de sospecha en pacientes con diagnóstico previo de tumores primarios de otra localización y realizar los estudios pertinentes según sea el caso 7 .…”
Section: Discussionunclassified
“…La manifestación clínica habitual comprende aumento de volumen doloroso, generalmente, similar a una infección de partes blandas con eritema, sensibilidad, calor local y limitación de la funcionalidad que puede evolucionar con empeoramiento progresivo de la lesión pudiendo adquirir un aspecto granulomatoso o asociado a ulceración 1,7 . Dada su presentación pueden simular granulomas piogénicos, artritis reumatoide, neoplasia primarias de piel como carcinoma de células escamosas, focos de osteomielitis, tofos gotosos, entre otros; debiendo tener un alto índice de sospecha en pacientes con diagnóstico previo de tumores primarios de otra localización y realizar los estudios pertinentes según sea el caso 7 .…”
Section: Discussionunclassified
“…1 The most frequent site of cutaneous metastasis of colonic cancer is the abdominal skin, often on surgical incision scars. This is not exclusive to the ad hoc surgical incision scar, but also to preexisting unrelated operative scars.…”
Section: Discussionmentioning
confidence: 99%
“…8 Uncommon reported sites of skin metastasis of colorectal cancer include scalp, face, eyelids, tip of the nose, nostril, forearm, genitalia, ankle and big toe. 1,2,4,8 Umbilical metastasis (Sister Mary Joseph's nodule) is a recurrent finding. 4,5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous metastasis is relatively rare in colorectal cancer (CRC). It has been reported that skin metastasis usually develops within two years after resection of the primary tumor [1][2][3]. Such metastasis indicates advanced stage and associated with poor prognosis due to suboptimal treatment and aggressive biological behavior of tumor.…”
Section: Introductionmentioning
confidence: 99%